Comprehensive Approach to Training English Communicative Competence in Chemistry - Kenzhe Aziza; Bitemirova Aliya; Ualikhanova Bayan; Bitursyn Saule; Zhorabekova Ainur (De Gruyter, 2024)
The development of foreign language professional communicative competence (FLPCC) is crucial for professionals, considering communicative skills as an integral part of their competence. In Kazakhstan, acquiring a foreign language is a prerequisite for advancing chemistry education, enabling students to access global scientific advancements and exchange knowledge. Content and language-integrated learning (CLIL) stands out as an effective approach for cultivating FLPCC in future chemistry teachers. This study addresses the scarcity of theoretical and practical tools in content-language integrated learning in pedagogical universities. It aims to enhance the training quality for pedagogy bachelor's degree students studying chemistry in a foreign language. By identifying active teaching forms, methodologies, and approaches in integrated learning, students' foreign language competence can be successfully developed within the professional domain. A meticulously designed training model and exercises were developed to achieve these goals. The proposed modeling approach was evaluated using the Quasi research method, involving questionnaire data analysis. The results confirm that implementing this approach significantly improves future chemistry professionals' training quality, enabling confident communication in English within their professional domains and demonstrating well-developed speaking skills. The practical value of this research extends to university educators implementing CLIL practices and researchers studying students' FLPCC formation.